Auditing mothers: The effect of targeted alcohol prevention on infant health and maternal behavior - Erik Grönqvist; Anna Norén; Anna Sjögren; Helena Svaleryd (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
This study examines the effects of targeted preventive interventions for pregnant women with elevated alcohol risk on infant health and maternal behavior. The detrimental effects of alcohol exposure in utero are well documented and universal alcohol prevention programs are an important part of national strategies to promote maternal and child health. Identifying effective interventions to prevent harmful maternal alcohol consumption is of great importance. We exploit the discrete nature in the decision rule to provide an alcohol preventive intervention to mothers at risk in a regression discontinuity design. The results suggest that the intervention has negligible impact on birth weight and small effects on the gestational age. We are unable to determine if this is due to a low effectiveness of the intervention or due to a low take up of the intervention.
Keywords: I12; I18; 330; Alcohol prevention; Brief intervention; AUDIT; Maternity care; Child health